PSIKOEDUKASI MENJAGA KESEHATAN MENTAL DIMASA PANDEMI COVID-19 - Ishaq Rahman; Rezky Nurul Fatihah (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2022)
Community empowerment is one of the efforts or processes to raise awareness, willingness and ability possessed by the community in recognizing, overcoming, protecting and improving the welfare of the community itself. Community empowerment can be realized in real work college activities or KKN. The work program created is to provide psychoeducation to the community, especially regarding maintaining mental health during the COVID-19 pandemic. The program was created to provide education to the public, especially mental health during the COVID-19 pandemic, this was done due to the lack of information obtained by the public regarding psychological conditions which also greatly impacted during the COVID-19 pandemic. The method used during the program is to distribute flyers to the public directly and through social media. The results obtained from programs that have been implemented are positive feedback given from the community, such as the community starting to feel a positive impact after implementing the tips that have been explained on the distributed flyer, the community also begins to understand how to manage stress during the covid-19 pandemic. Based on the program that has been made, it can be concluded that people are starting to realize the importance of maintaining mental health during the COVID-19 pandemic and getting information related to mental health